Trends in the diversification of the detergentome - Wycisk, Virginia; Wagner, Marc-Christian; Urner, Leonhard H. (Technische Universität Dortmund, 2023)
Detergents are amphiphilic molecules that serve as enabling steps for today's world applications. The increasing diversity of the detergentome is key to applications enabled by detergent science. Regardless of the application, the optimal design of detergents is determined empirically, which leads to failed preparations, and raising costs. To facilitate project planning, here we review synthesis strategies that drive the diversification of the detergentome. Synthesis strategies relevant for industrial and academic applications include linear, modular, combinatorial, bio-based, and metric-assisted detergent synthesis. Scopes and limitations of individual synthesis strategies in context with industrial product development and academic research are discussed. Furthermore, when designing detergents, the selection of molecular building blocks, i. e., head, linker, tail, is as important as the employed synthesis strategy. To facilitate the design of safe-to-use and tailor-made detergents, we provide an overview of established head, linker, and tail groups and highlight selected scopes and limitations for applications. It becomes apparent that most recent contributions to the increasing chemical diversity of detergent building blocks originate from the development of detergents for membrane protein studies. The overview of synthesis strategies and molecular blocks will bring us closer to the ability to predictably design and synthesize optimal detergents for challenging future applications.
ChemPlusChem; 89(1)
Keywords: amphiphiles; detergentome; detergents; lipids; membrane proteins; 570; 540